2021
DOI: 10.1021/acs.biomac.0c01599
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antibacterial Activity of Hen Egg-White Lysozyme against Staphylococcus aureus and Escherichia coli due to Protein Fibrillation

Abstract: Antibacterial agents with broad-spectrum antibacterial properties have always been in large demand. Lysozyme, a common and inexpensive protein, is widely used in food safety and biomedical applications for antibacterial purposes. However, many pathogens are lysozyme-resistant or insensitive. In this research, we investigated the antibacterial activities and mechanism of oligomers and amyloid fibrils formed from hen egg-white lysozyme (HEWL) against Staphylococcus aureus and Escherichia coli. The HEWL fibrils s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…The biofilm matrix mainly contains a variety of biological macromolecules such as extracellular polysaccharide, extracellular DNA (eDNA), enzymes, and other proteins. [ 107 ] Therefore, the destruction or elimination of biofilm‐related components is meaningful for biofilm breakdown. [ 108 ] For example, eDNA plays an important role in stabilizing bio0film structure and bacterial resistance, [ 109 ] and studies have shown that deoxyribonuclease I (DNase I) can hydrolyze effectively the eDNA of Gram‐positive bacteria and eukaryotic microorganisms, destroying the stability of young biofilms.…”
Section: Progress In Surface Modifications For Anti‐biofilmmentioning
confidence: 99%
“…The biofilm matrix mainly contains a variety of biological macromolecules such as extracellular polysaccharide, extracellular DNA (eDNA), enzymes, and other proteins. [ 107 ] Therefore, the destruction or elimination of biofilm‐related components is meaningful for biofilm breakdown. [ 108 ] For example, eDNA plays an important role in stabilizing bio0film structure and bacterial resistance, [ 109 ] and studies have shown that deoxyribonuclease I (DNase I) can hydrolyze effectively the eDNA of Gram‐positive bacteria and eukaryotic microorganisms, destroying the stability of young biofilms.…”
Section: Progress In Surface Modifications For Anti‐biofilmmentioning
confidence: 99%
“… 31 , 32 To this end, lysozyme has gained particular interest for its ability to rapidly form amyloid aggregates with broad spectrum antibacterial resistance. 33 36 This is of particular interest as lysozyme in its native form demonstrates little to no antibacterial efficacy against Gram-negative bacteria. 37…”
Section: Introductionmentioning
confidence: 99%
“…Protein amyloid fibrils are a class of elongated ordered supramolecular filaments, stabilized by β-sheet secondary structures, and formed via the self-assembly of protein/peptide fragments. Moreover, due to their flexible structure, amyloid fibers can also form entangled networks at relatively low concentrations, which is ideal for the formation of aerogels. , In general, protein amyloids are extremely versatile, due to the functional diversity in the protein/peptide moieties they are formed from; this has led to their application in areas such as catalysis, filtration, drug delivery, and biomimetic functional materials. , To this end, lysozyme has gained particular interest for its ability to rapidly form amyloid aggregates with broad spectrum antibacterial resistance. This is of particular interest as lysozyme in its native form demonstrates little to no antibacterial efficacy against Gram-negative bacteria…”
Section: Introductionmentioning
confidence: 99%
“…As one of the preferred natural antimicrobial agents in polyphenols, TA displays its antibacterial ability through inhibiting bacterial enzyme activity, reducing its stability and increasing the permeability through binding with the bacterial membrane, etc. 47–49 We speculate that TA in PEG–LZM–TA (DH) can improve the antibacterial properties of PEG–LZM too. In order to study the antibacterial properties of PEG–LZM–TA (DH), bacteria are cultured in the optimum environment in this experiment (bacteria culture medium concentration is 100%).…”
Section: Resultsmentioning
confidence: 99%